Differential effects of explicit and implicit corrective feedback on EFL learners' willingness to communicate. Issue 3 (3rd July 2018) - Tavakoli, Mansoor; Zarrinabadi, Nourollah
ABSTRACT: This sequential explanatory mixed methods study aimed at investigating the effect of explicit and implicit corrective feedback on Iranian English language learners' (EFL) L2 willingness to communicate (WTC) in English. Explicit and implicit corrective feedback were given to groups of low-intermediate Iranian EFL learners to see their effectiveness in facilitating L2 WTC. The findings of quantitative analysis were sequenced by follow-up qualitative data to explain the obtained results. The results of quantitative data analysis indicated that implicit corrective feedback did not influence L2 WTC, whereas explicit corrective feedback increased it. The analysis of qualitative data showed that explicit corrective feedback enhanced language learners' L2 WTC by promoting their L2 self-confidence. The implications of the study for language teachers and L2 WTC researchers are discussed.